Multivessel coronary-cameral fistulas associated with ventricular fibrillation: an unusual case - Abdulselam İlter; Eyyup Tusun; Abdulah Cirit (KARE Publishing, 2018)
Coronary-cameral fistula (CCF) is a rare connection between a coronary artery and a chamber of the heart. It most often derives from the right coronary artery and drains into the right ventricle. CCF originating from all 3 major coronary vessels and draining into the left heart is an extremely rare coronary artery malformation. A 47-year-old-man who was admitted to the clinic with angina pectoris and positive cardiac markers suddenly developed ventricular fibrillation (VF) while being prepared for coronary catheterization. He was successfully defibrillated and sinus rhythm was restored. The coronary angiography revealed normal epicardial coronary arteries with multiple diffuse fistulas originating from both the right and left coronary artery systems, terminating in the left ventricle. This is a very rare case of multiple CCFs originating from the epicardial coronary arteries and associated with myocardial ischemia and VF.